The internal condition in Ahwaz 1913-1925 - HAMEED ABO LOOL CHIBCHAB ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The study planned to recognize the workings of the problem of the Country of Arabi stan, through the political history of the Country of Arabi stan and the significance of its environmental and military area for the period from 1913 - 1925 Promotion, the idea of the approach of the Iranian government, and its use of counting strategies to tolerate its control of the Country of Arabi stan, and to distinguish the acts of the financial framework towards individuals of Arabistan through unfamiliar impedance in the interior, monetary and political undertakings, and the degree to which the rule of the right to self-assurance is taken advantage of to achieve the requests of individuals of the Country of Arabistan. The problem of the study alternated around a principle question: What is the idea of the Iranian strategy that tries to tolerate its control of the Country of Arabistan in the period between (1913-1925)? Pay individuals of the Country to guarantee the right to self-assurance? Through this question a bunch of sub-questions set. The assumption of the study demonstrated that Iranian strategy depends on trying to tolerate the control of the Country of Arabistan through system for restraint and misapplication to keep it from practicing their right to self-assurance. To confirm the theory and answer the inquiries of the study, the recorded strategy and the illustrative logical procedure were used, on the grounds that it is the most appropriate way to deal with address such studies. The study required a few suggestions, including: The self-determination of Arabistan must be a thorough disappointed, as it is the not unexpected intelligence to regenerate the opportunity of the area and achieve the potentials of individuals of the area to allowed them. The certain together war in the period 1913-1925, finishing the tourist existence in the country and the abuse of its monetary proceeds. DOI /10.54633/2333-021-042-022